Vak Vajra and His Contributions to the Buddhist Heritage of Thatu-Pui - Thapa, Prem (Journal of Buddhist Studies (T.U.), 2025)
Vak Vajra Vajracharya is considered one of the four patrons of Kathmandu’s Vajrayana Buddhist tradition. However, very little is known about him in Buddhist academic circles. Among the available descriptions of Vak Vajra, the majority take the form of legends and stories. This paper explores Vak Vajra’s historicity within these legends, shedding light on his life and works. The paper provides a brief introduction to the Vajracharya’s life, his main monastery, Kwā- bāha also known as Maitripur Mahavihara, and examines the period in which he flourished. The paper also describes his contributions, and explains how his works have influenced the living Vajrayana Buddhist heritage of Kathmandu’s Thathu: Pui (one of the four regions of Kathmandu). While there is no consensus on the exact period of his flourishing, this research analyzes available documents to determine the most plausible timeframe. Additionally, the paper uncovers previously unknown works of Vak Vajra Vajracharya. Through an exploratory analysis, this study adds valuable insights to the limited literature available on him.